EDUKASI PERENCANAAN MENU GIZI SEIMBANG PROGRAM DASHAT SEBAGAI UPAYA MENCEGAH STUNTING DI DESA LEUWIIPUH KECAMATAN BANJARSARI KABUPATEN LEBAK - Nikki Prafitri; Guruh Nata Sasmita; Dimas Septiyan Putra (Department of Public Administration, University Wijaykusuma Purwokerto, 2024)
Stunting is a nutritional problem that can interfere with the growth and development of children. Stunting cases are still occurring in Indonesia, including in Banjarsari District, Lebak Regency. One of the factors that causes stunting is the lack of public knowledge about nutritional fulfilment. In addition, not all villages have also implemented the Stunting Kitchen Program (DASHAT), which can be a community-based stunting prevention measure. Thus, education through counseling related to a balanced nutrition meal through the DASHAT program is important to prevent stunting. The purpose of this community service activity is to increase education on planning a balanced nutrition meal to prevent stunting in Leuwiipuh Village, because this village does not have stunting cases in Banjarsari District. Education was carried out to further strengthen efforts to prevent stunting as well as educate the public about the public about the importance of the formation of DASHAT. The result of this community service activity is that before education and material delivery, the knowledge of the target of the activity was still low, especially regarding local food sources, nutritional adequacy, food processing, and food safety aspects. After this educational activity, the knowledge of the target of the activity has increased to optimize the planning of healthy nutrition meal to prevent stunting.